Why Does the Face Predict the Brain? Neural Crest Induction, Craniofacial Morphogenesis, and Neural Circuit Development - LaMantia, Anthony-Samuel (Frontiers in Physiology, 2020)
Mesenchephalic and rhombencephalic neural crest cells generate the craniofacial skeleton, special sensory organs, and subsets of cranial sensory receptor neurons. They do so while preserving the A-P axial identity of their origin in the neural tube. This organizational principle is matched by central nervous system circuits that receive and process information from facial structures whose A-P identity is parallel to that in the brain. Prior to morphogenesis of the face and its circuits, however, neural crest cells act as “inductive ambassadors” from distinct regions of the neural tube to induce differentiation of target craniofacial domains, establishing an early interface between the brain and face. At every site of bilateral, non-axial secondary induction including craniofacial primordia, aortic arches, as well as the limbs and the brain and spinal cord themselves, neural crest constitutes the mesenchymal compartment for non-axial mesenchymal/epithelial (M/E) interactions and establishes local sources of inductive signaling molecules that drive interactions. This common mechanism for building brains faces, limbs, and hearts: A-P axis specified, neural crest-mediated M/E induction; coordinates differentiation of distal structures, peripheral neurons that provide their sensory or autonomic innervation in some cases, and central neural circuits that regulate their behavioral functions. The essential role of this neural crest-mediated mechanism identifies it as a prime target for pathological dysregulation in a broad range of neurodevelopmental disorders. Thus, the face and the brain “predict” one another, and this mutual developmental relationship provides a key target for disruption by developmental pathology.